EVALUASI PENYULUHAN MODEL SEKOLAH LAPANG TERHADAP PERUBAHAN PERILAKU PETANI PADI DI KECAMATAN JAWAI KABUPATEN SAMBAS - Laila Nuzuliyah; Darma Irawan (Politeknik Pertanian Negeri Kupang, 2022)
This study aims to determine the effectiveness of field school agricultural extension in improving the behavior of farmers in Sentebang Village, Jawai District, Sambas Regency. The extension technique used is the lecture method, discussion, demonstration, and filling out questionnaires. Respondents were given a pretest to determine the value of knowledge, attitudes, and skills before participating in field school activities. Then a posttest was given to determine the value of behavior change after attending field school. The effectiveness of changes in farmer behavior towards the field school model on rice plants was very effective in all three aspects of knowledge (78.1%), skills (72%), and attitudes (66.2%). The effectiveness of the evaluation of the field school model extension in the three aspects increased with the categories of knowledge (67.20%), skills (29.11%), and attitudes (19.33%).Keyword: evaluation, extension, farmer behavior